Improving students’ classroom participation through creative pedagogical strategies - Vanitha Thambirajah,; Melor Md Yunus,; Nur Ehsan Mohd Said, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Low-proficient students’ low performance in English as a second language (ESL) descriptive writing was observed to be related to their lack of participation in the teaching and learning process. This presents a need to explore alternative pedagogical strategies that could boost their participation, and thus their performance. This action research explored the effect of using creative pedagogical strategies on the classroom participation of 38 students at one of the secondary schools in Petaling Perdana District, Selangor. Focus group interviews, observation, and researcher’s reflective notes were utilised for data collection. Results show that students’ participation levels systematically improved at every cycle. Findings also revealed that the creative teaching strategies utilised caused active involvement in lessons and fostered cooperation among students in completing tasks. The multifarious materials and interactive tasks used during the lessons inspired communication and discussions among students. Learning from multiple resources provides enthusiasm to learn among students. Lastly, teaching strategies that require active participation developed positive mindset that developed positive attitude towards learning among the students. In conclusion, creative pedagogical strategies that are based on the students’ learning needs have a straightforward and positive effect on boosting the students’ participation in learning.